2014
DOI: 10.1080/10408398.2012.724480
|View full text |Cite
|
Sign up to set email alerts
|

Ochratoxin A and Human Health Risk: A Review of the Evidence

Abstract: Ochratoxin A (OTA) is a mycotoxin produced by several fungal species including Aspergillus ochraceus, A. carbonarius, A. niger and Penicillium verrucosum. OTA causes nephrotoxicity and renal tumors in a variety of animal species; however, human health effects are less well-characterized. Various studies have linked OTA exposure with the human diseases Balkan endemic nephropathy (BEN) and chronic interstitial nephropathy (CIN), as well as other renal diseases. This study reviews the epidemiological literature o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
162
1
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 309 publications
(193 citation statements)
references
References 54 publications
1
162
1
5
Order By: Relevance
“…OTA had been implicated in an endemic kidney disease observed in Eastern Europe (Balkan Endemic Nephropathy and related urinary tract tumors), but convincing epidemiological evidence associating this disease with OTA exposure is lacking (Bui-Klimke and Wu 2014). A systematic review of the epidemiological studies linking OTA with adverse effects in humans showed no evidence linking the two, except for one preliminary study (Wafa et al 1998) in which, unusually high OTA-exposed individuals also had a higher risk of nephritic syndrome (Bui-Klimke and Wu 2015). However, that study did not control for other potential risk factors, such as bacterial or viral infection, diabetes, lupus, and high blood pressure.…”
Section: Introductionmentioning
confidence: 99%
“…OTA had been implicated in an endemic kidney disease observed in Eastern Europe (Balkan Endemic Nephropathy and related urinary tract tumors), but convincing epidemiological evidence associating this disease with OTA exposure is lacking (Bui-Klimke and Wu 2014). A systematic review of the epidemiological studies linking OTA with adverse effects in humans showed no evidence linking the two, except for one preliminary study (Wafa et al 1998) in which, unusually high OTA-exposed individuals also had a higher risk of nephritic syndrome (Bui-Klimke and Wu 2015). However, that study did not control for other potential risk factors, such as bacterial or viral infection, diabetes, lupus, and high blood pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Ochratoxin A (OTA) is produced by different species of fungi including A. ochraceus, A. carbonarius, A. niger and P. verrucosum, and it is an important food-borne mycotoxin that occurs in a wide variety of agricultural commodities ranging from cereal grains to dried fruits, to wine and coffee. Contamination generally occurs as a result of poor storage of commodities and suboptimal agricultural practices during the drying of foods (Bui-Klimke & Wu 2015;Marin & Taranu 2015). On the whole, mycotoxins contaminate a wide range of agricultural products, such as cereals, beans, oil seeds and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Although the causative relation is still to be proven, a significantly higher exposure to OTA was proven for inhabitants from endemic regions than control regions [32]. However,further studies are need to better understand the role of ochraotxin A exposure in renal diseases [33,34].…”
Section: Adverse Effects Of Mycotoxins On Humansmentioning
confidence: 99%